Promoting health for working women (Berlin, 2008)
"Based on European health initiatives on reducing workplace risks and promoting workplace health, Promoting Health for Working Women focuses on issues that predominantly or exclusively affect women, or have gender-specific implications because of differences or special circumstances that exist at the workplace. The editors and their twenty collaborators combine theoretical, research, and practical perspectives to create a framework for studying female workers’ health issues and risks. The methodology for organizing on-site health promotion interventions at the workplace is presented in detail, taking into consideration the key issues women face. Among the topics covered in Promoting Health for Working Women: - Legal foundations for workers’ safety, in general and by gender. - Occupational hazards, musculoskeletal injuries, communicable diseases. - Work-life balance issues, including stress, burnout, and depression. - Violence, bullying, and sexual harassment on the job. - Special focus on pregnancy and breastfeeding. - Screening at the workplace. - Smoking cessation, alcohol awareness, diet/exercise, and other lifestyle concerns."